Digital platforms and the SDGs: A socio-eco-technical framework for SMEs based on cross-case analysis - Carmen Isensee; Frank Teuteberg; Kai-Michael Griese (Corporate Social Responsibility and Environmental Management, 2024)
Managing the complex relationship between digitalization and sustainable development is a key challenge for many small and medium sized enterprises (SMEs). To understand strategies of forerunners in the field of digital platforms and platformization, this study performs a cross-case analysis of three sustainability-oriented SMEs employing multi-sided platforms operating in three sectors (wholesale, information and communication technology, and construction) in Germany. The integrated analysis framework draws from Belief-Action-Outcome theory, multi-sided platform strategies, and the sustainable development goals (SDG). The findings identify four platformization strategies and exemplarily specify contributions to SDG 2, 7, 8, 9, 12, 13, and 17. The proposed socio-eco-technical framework emphasizes linkages between an employed platformization strategy (technical system), the corporate culture (social system), the platform stakeholders and the SDGs (ecological system). A seven-step approach is proposed to motivate and facilitate the development and continuous improvement of platformization for sustainability in SMEs.
Keywords: 650; case study; corporate culture; digital platform; SDGs; SMEs; socio-technical systems